The age of the Lower Paleolithic occupation at Schöningen. Issue 89 (December 2015) - Richter, Daniel; Krbetschek, Matthias
Abstract: Thermoluminescence (TL) data are presented for eight samples of heated flint collected at the archaeological site of Schöningen 13/I-1 (Cycle I), for which a Holsteinian age is suggested by palynology of stratigraphically similar positions within a cyclic sedimentological model for the Quaternary sequence of Schöningen. Although the fire responsible for the zeroing of the TL-signal cannot be unequivocally attributed to human activities, any time difference between a natural fire and the human occupation is negligible for a site of this antiquity. The weighted mean age of 321 ± 16 ka places the last heating of the flints nominally in the age range of Marine Isotope Stages (MIS) 10 to 8. By inference this data would suggest an attribution of the Holsteinian to MIS 9 and may also serve as a maximum age estimate for the spear site of Schöningen 13/II-4 (Cycle II). Considering the chronometric data available and following an alternative sedimentological model the age of these two sites at Schöningen can be considered as belonging to the same climatic cycle. This suggests an attribution to MIS 9, and by inference provides an age estimate of 337–300 ka for the oldest spears in human history.